PENGARUH SOCIAL SUPPORT TERHADAP SELF-EFFICACY NARAPIDANA THERAPEUTIC COMMUNITY LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS IIA JAKARTA - Chintiani Bokko, Elsywenda Gloria; Rahayu, Mulyani (Universitas Nusa Cendana, 2024)
During the Therapeutic Community, prisoners need social support to be able to increase the level of self-efficacy during the Therapeutic Community program. The purpose of this study is to determine and examine the effect of social support on the self-efficacy of Therapeutic Community prisoners in Class IIA Jakarta Correctional Institution. The number of samples studied was 132 responses. The method used in this study is to use quantitative sampling techniques with Probability Sampling with the type of Cluster Random Sampling. The results obtained a coefficient of determination (R-Square) of 0.526 which contains the understanding that the influence of the independent variable (social support) on (self-efficacy) is 52.6%. The significance test showed the effect of social support on the self-efficacy of Therapeutic Community prisoners in Class IIA Jakarta Narcotics Correctional Institution Keywords: Social Support; Self-Efficacy; Therapeutic Community